Agile Software Development with Secure and Scrum-Centric Approach - Ömer Kasım (Online Academic Journal of Information Technology)
The fulfillment of agile models is crucial for ensuring that a software development project's tasks are completed efficiently and collaboratively. The definitions of the project architecture are usually performed in these models. Factors such as delivery time, cost and maintenance are determined. In traditional methods, project stages are carried out sequentially. After one of the stages is completed, another one is performed. When an innovation or change is attempted at any point in the project, some problems occur. These problems can generally be solved with Scrum agile methods, where communication is highlighted and processes are performed more flexibly. It is an undeniable fact that Scrum and security issues can be brought together when incorporating the Scrum strategy into software development models. In such a case, models are used that allow Security and Scrum to work within a framework. In this study, scientific studies based on scientific evidence aimed at eliminating incompatibilities in software development systematics were analyzed. The distribution of the publication years, the relation of scrum and security, the citation topic, the bibliometric maps and co-citation report are used in these analysis. In the result of these analyses, bibliometric and statistical analysis results of studies in the literature on software development that includes security principles with the Scrum model were revealed. When the results obtained in the experiments were examined, it was concluded that it was possible to develop secure software with an architecture in which Scrum and Security models were used together. During the software development phase, it enables proactive risk management by blending scrum and security elements. It also allows teams to detect security vulnerabilities during the software development phase. These facilitate the creation of a more secure and durable software product.